Design and Implementation of Patient Monitoring System for Medical Sign using GSM and Microcontroller - Reem Jamal Abbas; Rawaa Abdel Ridha kadhim; Siraj Qays Mahdi (Journal of Madenat Alelem University College, 2017)
The work presented in this paper concerned with the design of a new remote monitoring system for patients in An intensive care unit (ICU) , which can be used to read the medical signs such as (heart rate, temperature value and oxygen saturation percentage) from the patient's body beside checking the pacemaker device and send the values to the remote area. The proposed system deals with the patient vital signs as an input to send them to a computer in the nursing room by a transmitter-receiver system which composed of two Arduino kits connected with Bluetooth devices. The signal received by computer is processed and if there is an abnormal condition a message will be send to doctor mobile through Global System for Mobile Communications (GSM). The mechanism of the system is to send the medical signs to doctors in a remote area. Tإhe computer sends these values to doctor's mobile. Finally, visual basic language was used to implement the frame work of the system.